A Hospital Based Comparative Study of Serum Magnesium in Obese Versus Non Obese Children - SEKAR PASUPATHY; POORNIMA; MAHARAJA PANDIAN (International Journal of Pharma and Bio Sciences, 2018)
It is known that obesity and metabolic syndrome begin in the childhood and is tracked further into adulthood. This study was conducted to test the hypothesis of the association of lower serum magnesium with obesity. Magnesium deficiency and obesity has been associated with insulin resistance and increased incidence of type 2 diabetes in adults. The aim of present prospective analytical case study is to estimate the serum magnesium level in children with obesity and to compare it with non obese children.The study was done on 144 children for a period starting from Feb 2015 to Sep 2015. The children included both inpatients and outpatients of the paediatrics department of the SRM Medical College Hospital. Of these 72 children were diagnosed to have obesity and the other 72 were non obese children. Serum magnesium levels were estimated in all 144 subjects by using calorimetric methods. Data was analyzed using mean standard deviation Pearson chi square test and SPSS version 20.Mean serum magnesium level in children with obesity was 1.461mgm/dl and mean serum magnesium level in control group was 2.660 mg /dl (p=0.000). There were no significant differences based on age and gender.The findings revealed that there is a correlation between serum magnesium and obesity. Serum magnesium level was obviously lower in obese children in comparison with non obese children.